Caspase-4 and -5 Biology in the Pathogenesis of Inflammatory Bowel Disease - Smith, Aoife P.; Creagh, Emma M. (Frontiers in Pharmacology, 2022)
Inflammatory bowel disease (IBD) is a chronic relapsing inflammatory disease of the gastrointestinal tract, associated with high levels of inflammatory cytokine production. Human caspases-4 and -5, and their murine ortholog caspase-11, are essential components of the innate immune pathway, capable of sensing and responding to intracellular lipopolysaccharide (LPS), a component of Gram-negative bacteria. Following their activation by LPS, caspases initiate potent inflammation by causing pyroptosis, a lytic form of cell death. While this pathway is essential for host defence against bacterial infection, it is also negatively associated with non-infectious inflammatory pathologies. Caspases-4/-5/-11 display increased intestinal expression during IBD and have been implicated in chronic IBD inflammation. This review discusses the current literature in this area, identifying links between inflammatory caspase activity and IBD in both human and murine models. Differences in the expression and function between caspases-4, -5 and -11 are discussed, in addition to mechanisms of their activation, function and regulation, and how these mechanisms may contribute to the pathogenesis of IBD.